Gas Emergency Policy Where do IEA Countries Stand? - Simpson, James (IEA Energy Papers, 2011)
Natural gas is of increasing importance in the energy mix of IEA Member countries. And yet this growing reliance on natural gas has been coupled with an increased risk of gas disruptions in recent years. Gas security is now an important policy concern for many IEA Member countries, and the IEA has sought to develop its expertise and analysis in this field.This Working Paper looks at the possible remedies that are available for dealing with gas security concerns, and takes stock of developments in gas emergency policy in IEA Member countries